New approach to address antibiotic resistance: Miss loading of functional membrane microdomains (FMM) of methicillin-resistant Staphylococcus aureus (MRSA). (February 2019) - Nagendra Prasad, H.S.; Karthik, C.S.; Manukumar, H.M.; Mallesha, L.; Mallu, P.
Abstract: The synthesized potent piperazine analog ChDiPiCa was characterised by various spectroscopic techniques and for the first time evaluated functional membrane microdomain (FMM) disassembly in methicillin-resistant Staphylococcus aureus (MRSA). The ChDiPiCa showed excellent in vitro biocidal activity against MRSA at 26 μg/mL compared to the antibiotic streptomycin and bacitracin 14 μg/mL and 13 μg/mL at 10 μg concentration respectively. The membrane damaging property was confirmed by the SEM analysis. Further, we addressed the new approach for the first time to overcome antibiotic resistance of MRSA through membrane microdomain miss loading to lipids. By which, the ChDiPiCa confirms the significant activity in miss loading of FMM of MRSA which is validated by the fatty acid profile and lipid analysis. The result shows that, altered saturated (Lauric acid and Myristic acid), mono unsaturated (Oleic acid), and poly unsaturated (Linoleic acid and Linolenic acid) fatty acids and hypothesises, altered the membrane functional lipids. For the better understanding of miss loading of FMM by the ChDiPiCa, the in-silico molecular docking studies was analyzed and confirmed the predicted role. This suggests the way to develop ChDiPiCa in medicinal chemistry as anti-MRSA candidates and also this report opens up new window to treat microbial pathogens and infections. Graphical abstract: Image 1 Highlights: The designed novel piperazine analog ChDiPiCa showed biocidal nature against MRSA. ChDiPiCa addressed to understand the functional membrane microdomains (FMM) disassembly against MRSA for the first time. The new way to overcome antibiotic resistance in MRSA through FMM unloading approach was hypothesized. The FMM misloading approach open a new door in medicinal chemistry against infectious agents.